Comparação da transmissão de força miofascial entre os músculos grande dorsal e glúteo máximo em corredores e sedentários: um estudo transversal - Paola de Figueiredo Caldeira (2023)
Myofascial force transmission (MFT) has already been demonstrated in cadavers and in vivo in different regions of the musculoskeletal system, such as between the latissimus dorsi (LD) and gluteus maximus (GM) muscles. The efficiency of MFT appears to be influenced by tissue passive characteristics. It is known that the mechanical stimulus induced by regular physical activity can induce changes in the stiffness of biological tissues and it is possible that specific physical and sporting activities, such as running, may require greater use of the force transmission pathway between LD and GM. The sports gesture of running involves a coupled movement of shoulder extension on one side and contralateral hip extension, a moment in which the action of the LD and GM muscles can generate an increase in tension in the thoracolumbar fascia, stimulating MFT between the muscles. Considering this movement pattern and the fact that runners have greater tissue stiffness, it is possible that runners have greater MFT between LD and GM when compared to sedentary people. The objectives of the present study were to investigate whether (1) the contraction of the LD during shoulder extension modifies the stiffness of the lumbar region, and the passive properties of the contralateral hip in runners and sedentary people, which would indicate the occurrence of MFT and (2) to verify whether this MFT is higher in runners than in sedentary people. 54 individuals participated in this study, 27 in each group. Assessments of lumbar stiffness were carried out with a myothonometer and of the passive properties of the hip (hip resting position, passive hip torque, and passive hip stiffness) with the isokinetic dynamometer in two test conditions: LD relaxed and LD contracted. Mixed analysis of variance was used to evaluate the main and interaction effects for the variables lumbar stiffness, hip resting position, passive hip torque, and stiffness. In the presence of an interaction effect, pre-planned contrasts were used to investigate the direction of the interactions. Runners had a more pronounced increase in lumbar stiffness during LD contraction (p = 0.017). Furthermore, LD contraction led to a change in the resting position of the hip towards external rotation and an increase in torque and passive hip stiffness in both groups. Thus, the results of the study demonstrated that MFT occurred in both groups. The analyzes also demonstrated that, although the magnitude of the change in lumbar stiffness was greater in runners, the MFT was not greater in this group when compared to the sedentary group. As far as we know, this was the first study to carry out this analysis, therefore, it is necessary to develop research that carries out this investigation through, for example, elastography, and that analyzes other factors, such as the effect of GM tension in lumbar stiffness and MFT in the direction of GM contraction for the contralateral LD in runners and sedentary people.